If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(x + -9)(4x + -3) = 0 Reorder the terms: (2 + x)(x + -9)(4x + -3) = 0 Reorder the terms: (2 + x)(-9 + x)(4x + -3) = 0 Reorder the terms: (2 + x)(-9 + x)(-3 + 4x) = 0 Multiply (2 + x) * (-9 + x) (2(-9 + x) + x(-9 + x))(-3 + 4x) = 0 ((-9 * 2 + x * 2) + x(-9 + x))(-3 + 4x) = 0 ((-18 + 2x) + x(-9 + x))(-3 + 4x) = 0 (-18 + 2x + (-9 * x + x * x))(-3 + 4x) = 0 (-18 + 2x + (-9x + x2))(-3 + 4x) = 0 Combine like terms: 2x + -9x = -7x (-18 + -7x + x2)(-3 + 4x) = 0 Multiply (-18 + -7x + x2) * (-3 + 4x) (-18(-3 + 4x) + -7x * (-3 + 4x) + x2(-3 + 4x)) = 0 ((-3 * -18 + 4x * -18) + -7x * (-3 + 4x) + x2(-3 + 4x)) = 0 ((54 + -72x) + -7x * (-3 + 4x) + x2(-3 + 4x)) = 0 (54 + -72x + (-3 * -7x + 4x * -7x) + x2(-3 + 4x)) = 0 (54 + -72x + (21x + -28x2) + x2(-3 + 4x)) = 0 (54 + -72x + 21x + -28x2 + (-3 * x2 + 4x * x2)) = 0 (54 + -72x + 21x + -28x2 + (-3x2 + 4x3)) = 0 Combine like terms: -72x + 21x = -51x (54 + -51x + -28x2 + -3x2 + 4x3) = 0 Combine like terms: -28x2 + -3x2 = -31x2 (54 + -51x + -31x2 + 4x3) = 0 Solving 54 + -51x + -31x2 + 4x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| x^2-4x=x(8+x) | | 14.0-2.4=1.5(x+0.15-3.5+0.1) | | m+2+6=10 | | (7x-5)(3x+5)= | | (x+4)(2x-7)=18 | | m+8+6=28 | | 3/5x-5=-2 | | 40x/10=4 | | (x+4)(2x-7)=36 | | y=[x-(-6-3i)][x-(-6+3i)] | | y=[x-(6-3i)][x-(6+3i)] | | 3d^2+20d-25=0 | | b^2+9b+22=0 | | 4x+5y=-25 | | -a^2-2a+99=0 | | 5-2y/3=25/12-5y-3/4 | | -2a^2+28a-80=0 | | 7-x/3=4-x | | x+6y=29 | | 0.25x^2-2x+3=0 | | 5x-2/3=1/6 | | (-6y+29)-4y=-6 | | Vw+3v=2w+5 | | 1.25x^2-2x+3=0 | | 2x+3xy-2xy+3x= | | n+2(9+5n)= | | 9x-5x+3x+4x=63 | | x*ln(x^2)+ln(2)=0 | | (16/25)^-3/2 | | 16/25^-3/2 | | y^4+9y^2-100=0 | | (16/25)^(-3/2) |